Strategi Sourcing Berkelanjutan MBG Berbasis Advanced Analytics: Analisis PESTLE dan Rantai Pasok - Briyan Gifari; Nabiel Muhammad Al Ghazali; Abdullah Fajar (SOTVI - Society of Visual Informatics, 2026)
The Free Nutritious Meal Program (MBG) is a national strategic initiative facing complex challenges in balancing supply security and environmental sustainability. This study aims to implement an Advanced Analytics framework to evaluate supplier performance based on the Triple Bottom Line principle. Using real logistics datasets for strategic commodities (Rice and Soybeans), this study applies the Weighted Scoring Model algorithm with parameters of logistics efficiency (40%), environmental impact (30%), and volume security (30%). The analysis of the supply chain shows a total carbon footprint (Scope 3) of 112.11 tons of CO2 with an average distribution distance of 297 KM. The model successfully identified the best